Direct interactions of coxsackievirus B3 with immune cells in the splenic compartment of mice susceptible or resistant to myocarditis. - Anderson, D R (1996)
In vitro replication of coxsackievirus B3 (CVB3) in cells of the immune system derived from uninfected adolescent A/J and C57BL/6J mice and replication of CVB3 in and association with immune cells from spleens of infected animals in vivo were assessed. Nonstimulated or mitogen-stimulated spleen cells were minimally permissive for viral replication during an 8-h period. Three days postinfection (p.i.), CVB3 RNA was localized in vivo to B cells and follicular dendritic cells of germinal centers in both A/J and C57BL/6J mice; however, extrafollicular localization was greater in C57BL/6J mice (P = 0.0054). Although the pattern of CVB3 RNA localization was different, the total load of infections virus (PFU per milligram of tissue) was not different. Splenic CVB3 titers (PFU per milligram of tissue) in both strains were maximal at day 3 or 4 p.i. and were back to baseline by day 7 p.i., with most infectious virus being non-cell associated. CVB3 titers (PFU per milligram of tissue) correlated directly with in situ hybridization positivity in splenic follicles and extrafollicular regions in both murine strains; however, follicular hybridization intensity was greater in A/J mice at day 5 p.i. (P = 0.021). Flow cytometric analysis demonstrated that 50.4% of total spleen cells positive for CVB3 antigen were B cells and 69.6% of positive splenic lymphocytes were B cells. Myocardial virus load in C57BL/6J mice was significantly lower than that in A/J mice at days 4 and 5 p.i. These data indicate that CVB3 replicates in murine splenocytes in vitro and in B cells and extrafollicular cells in vivo.